Perspectives for Applying International Experience of Audit of Financial Investments (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
This article is devoted to the consideration of the perspectives of developing the audit of financial investments in reliance upon foreign experience. In addition, the article analyzes the perspectives of the investment policy in our republic and development of accounting and audit of investments in reliance upon international experience. Moreover, the stages of conducting the audit in the formation of reliable audit opinions on the objects of financial investments have been developed. Furthermore, based on the proposals and recommendations, the transparency of the audit by including additional activities in the audit of financial investments has been ensured.